How does port intelligence impact the performance of port firms?–Empirical evidence from listed port firms in China - Fu, Dandan; Ishak, Suryati; Bani, Yasmin; Ma, Xiaoya; Dapo, Olohunlana Somod (Routledge, 2025)
With the fast growth of digital economy, intelligent technology plays a vital role in enterprise transformation and upgrading, and its impact on enhancing firm performance has attracted significant attention. Based on panel data of 16 Chinese A-share listed port firms from 2013 to 2021, this article takes ‘the 2017 Smart Port Demonstration Project’ as a quasi-natural experiment. It employs the Propensity Score Matching-Difference in Differences (PSM-DID) method to examine the influence and mechanisms of port intelligence on the performance of port firms. The research findings indicate that port intelligence significantly influences the performance of port firms, and this result is supported by various robustness checks. Technological innovation and firm resilience emerge as the primary mechanisms through which port intelligence positively influences the performance of port firms. The empirical evidence offers new insights into the causal mechanisms between port intelligence and the performance of port firms, and provides valuable implications for improving the performance of port firms.